Analisis Kesulitan Belajar Membaca, Menulis, Dan Matematika Pada Siswa Kelas 5 SD: Studi Kualitatif Di Bandung - Nabillah Salsabila; Endang Rochyadi; Nita Nitiya Intan Tanbrin (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This study aims to analyze the learning difficulties faced by 5th-grade students at SD Negeri Bandung in reading, writing, and arithmetic. The analysis revealed that the majority of students are at a frustration level in all three aspects, indicating a lack of fundamental understanding. This study also highlights the urgent need for more comprehensive and systemic educational reforms, focusing on improving teaching quality, adaptive learning methods, and holistic support for students. In conclusion, enhancing the quality of basic education and employing more inclusive teaching methods are crucial to address the varying levels of student abilities and learning styles.